Alcohol Withdrawal Syndrome: Improving Recognition and Treatment in the Emergency Department. (January 2019) - Glann, Judith K.; Carman, Margaret; Thompson, Julie; Olson, David; Nuttall, Cynthia; Fleming, Holly; Reese, Cheryl
Abstract : Alcoholism continues to be a persistent health problem in the United States, accounting for up to 62% of emergency department (ED) visits. This quality improvement (QI) project examined whether identifying the benefit for early use of Alcohol Use Disorders Identification Test (AUDIT C) and Clinical Institute Withdrawal Assessment of Alcohol Scale, Revised (CIW-ar) in the ED would avoid escalation of care and offset poor outcomes of alcohol withdrawal syndrome (AWS). A preimplementation chart review ( N = 99) showed an average of 12%–15% of patients requiring escalation of care at the project site. The QI project utilized a single-group, pre-/posttest design. The setting was a Southwest Veterans Affair tertiary care referral center. Thirty-five ED staff members were surveyed for baseline knowledge and attended education sessions, led by an advanced practice nurse, on the use of AUDIT-C and CIWA-ar. Posteducation, patients admitted to the hospital were screened with AUDIT-C and treated with CIWA-ar. Postimplementation, charts were reviewed for admitted patients ( N = 42) on the use of AUDIT-C, CIWA-ar, length of stay (LOS), and area patient treated. Although the test scores after didactic education were statistically significant ( p ⩽ 0.050), there was no significant difference in the use of AUDIT-C or CIWA-ar in the ED, nor a significant decrease in LOS for those patients with CIWA-ar ordered. However, the potential for clinical benefit could not be disavowed. Barriers to implementation included survey fatigue, inability to embed AUDIT-C in the electronic medical record, inconsistency in completing AUDIT-C, interrater reliability, and patient fear of stigmatization. Advanced practice nurses provide an integral role to augment early identification and treatment of AWS in the ED.